2021
DOI: 10.1021/acsaem.1c00887
|View full text |Cite
|
Sign up to set email alerts
|

Polyether Ether Ketone-Based Anion Exchange Membranes with Bis-imidazolium Cations for All-Vanadium Redox Flow Batteries

Abstract: In this study, a series of polyether ether ketone (PEEK)-based un-cross-linked and cross-linked anion exchange membranes (AEMs) with bisimidazolium cations are prepared to fabricate all-vanadium redox flow batteries (VRFBs). Compared with a Nafion 212 membrane, these AEMs exhibit significantly lower vanadium-ion permeabilities because of the Donnan exclusion effect of bis-imidazolium cations. Moreover, owing to their denser structure, the vanadium permeability of the cross-linked PEEK-based AEMs (CImPEEK) is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In detail, the mechanical strength and elongation of the PVAc-0.5BPTMA-0.5DBPX-GA membrane were 10.3 MPa and 4.9%, while those of the PVAc-0.5BPTMA-0.5DBPX membrane were 5.1 MPa and 104.8%. Since the tensile strength of the membrane is a crucial indicator for longtime operation in VFBs, 25 GA cross-linking is an effective method to improve the dimensional and mechanical stabilities.…”
Section: Fabrication Of Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, the mechanical strength and elongation of the PVAc-0.5BPTMA-0.5DBPX-GA membrane were 10.3 MPa and 4.9%, while those of the PVAc-0.5BPTMA-0.5DBPX membrane were 5.1 MPa and 104.8%. Since the tensile strength of the membrane is a crucial indicator for longtime operation in VFBs, 25 GA cross-linking is an effective method to improve the dimensional and mechanical stabilities.…”
Section: Fabrication Of Membranesmentioning
confidence: 99%
“…Zhang et al prepared a series of bis(imidazolium)-containing PEEK-based AEMs, which exhibited the low VO 2+ permeability, resulting in a higher CE of 99.5% than Nafion 212 (∼95.8%) at 120 mA cm −2 . 25 It is reported that aryl ether free AEMs possessed the enhanced chemical resistance as demonstrated by quaternary ammonium (QA) grafted polybenzimidazole- 26,27 and poly-(terphenylene)-based 28,29 AEMs. Additionally, in our recent work, it is interesting to find that AEMs based on QA side chain functionalized poly(p-terphenyl-N-methylpiperidinium)s exhibited high H + permeability.…”
Section: Introductionmentioning
confidence: 99%
“…So far, because of its extraordinarily high conductivity and outstanding chemical stability, Nafion membranes are still one of the finest choices for VRFB ion-selective membranes . However, the drawbacks of a high expansion rate, substantial vanadium ion penetration, and high cost are the key issues for large-scale deployment of Nafion membranes in VRFBs. , Many efforts have been made to date to produce innovative ion-selective membranes with improved performance and cheaper costs, such as cross-linking-modified and polymer-blended composite membranes. Because of their low cost, stability, and ease of manufacture, sulfonated poly­(ether ether ketone) membranes (SPEEK) have received a lot of interest. ,,, Amphoteric ion exchange membranes with fixed cations and anion exchange groups have received a lot of interest in recent years. , Due to electrostatic repulsion, the positive ion group can effectively prevent the positive diffusion of vanadium ions under battery operating conditions, while the negative ion group provides optimum proton conductivity. Sulfamic acid (SA) contains −SO 3 H (acidic) and −NH 2 (weak basic) groups, which can be used to replace the inherent conductivity/permeability balance of the proton exchange membrane …”
Section: Introductionmentioning
confidence: 99%
“…Xing et al 13 prepared a series of poly(sulfone)-based AEMs modified by C2-protected imidazolium through an efficient Cu( i )-catalyzed azide–alkyne cycloaddition reaction, and the membranes exhibited excellent durability. Yang et al 17 fabricated a series of polyether ether ketone (PEEK)-based AEMs with bis imidazolium through complex reactions. The above-mentioned AEMs showed very high coulombic efficiency, indicating their great potential for application in VRFBs.…”
Section: Introductionmentioning
confidence: 99%